let k, m, n be Nat; :: thesis: for K being Field
for V being VectSp of K
for M1 being Matrix of n,k, the carrier of V
for M2 being Matrix of m,k, the carrier of V holds Sum (M1 ^ M2) = (Sum M1) ^ (Sum M2)

let K be Field; :: thesis: for V being VectSp of K
for M1 being Matrix of n,k, the carrier of V
for M2 being Matrix of m,k, the carrier of V holds Sum (M1 ^ M2) = (Sum M1) ^ (Sum M2)

let V be VectSp of K; :: thesis: for M1 being Matrix of n,k, the carrier of V
for M2 being Matrix of m,k, the carrier of V holds Sum (M1 ^ M2) = (Sum M1) ^ (Sum M2)

let M1 be Matrix of n,k, the carrier of V; :: thesis: for M2 being Matrix of m,k, the carrier of V holds Sum (M1 ^ M2) = (Sum M1) ^ (Sum M2)
let M2 be Matrix of m,k, the carrier of V; :: thesis: Sum (M1 ^ M2) = (Sum M1) ^ (Sum M2)
A1: dom (Sum (M1 ^ M2)) = Seg (len (Sum (M1 ^ M2))) by FINSEQ_1:def 3;
A2: now :: thesis: for i being Nat st i in dom (Sum (M1 ^ M2)) holds
(Sum (M1 ^ M2)) . i = ((Sum M1) ^ (Sum M2)) . i
let i be Nat; :: thesis: ( i in dom (Sum (M1 ^ M2)) implies (Sum (M1 ^ M2)) . i = ((Sum M1) ^ (Sum M2)) . i )
assume A3: i in dom (Sum (M1 ^ M2)) ; :: thesis: (Sum (M1 ^ M2)) . i = ((Sum M1) ^ (Sum M2)) . i
then i in Seg (len (M1 ^ M2)) by ;
then A4: i in dom (M1 ^ M2) by FINSEQ_1:def 3;
now :: thesis: (Sum (M1 ^ M2)) . i = ((Sum M1) ^ (Sum M2)) . i
per cases ( i in dom M1 or ex n being Nat st
( n in dom M2 & i = (len M1) + n ) )
by ;
suppose A5: i in dom M1 ; :: thesis: (Sum (M1 ^ M2)) . i = ((Sum M1) ^ (Sum M2)) . i
len M1 = len (Sum M1) by Def6;
then A6: dom M1 = dom (Sum M1) by FINSEQ_3:29;
thus (Sum (M1 ^ M2)) . i = (Sum (M1 ^ M2)) /. i by
.= Sum ((M1 ^ M2) /. i) by
.= Sum (M1 /. i) by
.= (Sum M1) /. i by A5, A6, Def6
.= (Sum M1) . i by
.= ((Sum M1) ^ (Sum M2)) . i by ; :: thesis: verum
end;
suppose A7: ex n being Nat st
( n in dom M2 & i = (len M1) + n ) ; :: thesis: (Sum (M1 ^ M2)) . i = ((Sum M1) ^ (Sum M2)) . i
A8: len M1 = len (Sum M1) by Def6;
len M2 = len (Sum M2) by Def6;
then A9: dom M2 = dom (Sum M2) by FINSEQ_3:29;
consider n being Nat such that
A10: n in dom M2 and
A11: i = (len M1) + n by A7;
thus (Sum (M1 ^ M2)) . i = (Sum (M1 ^ M2)) /. i by
.= Sum ((M1 ^ M2) /. i) by
.= Sum (M2 /. n) by
.= (Sum M2) /. n by
.= (Sum M2) . n by
.= ((Sum M1) ^ (Sum M2)) . i by ; :: thesis: verum
end;
end;
end;
hence (Sum (M1 ^ M2)) . i = ((Sum M1) ^ (Sum M2)) . i ; :: thesis: verum
end;
len (Sum (M1 ^ M2)) = len (M1 ^ M2) by Def6
.= (len M1) + (len M2) by FINSEQ_1:22
.= (len (Sum M1)) + (len M2) by Def6
.= (len (Sum M1)) + (len (Sum M2)) by Def6
.= len ((Sum M1) ^ (Sum M2)) by FINSEQ_1:22 ;
hence Sum (M1 ^ M2) = (Sum M1) ^ (Sum M2) by ; :: thesis: verum